Functional Impact of Interleukin -33 Polymorphism on IRF8 and TGF-β Regulation in Leukemia Patients - Al-Sugmiany, Rafea Zaidan Mukhlif; Kamil, Noor Rassam; Huseein, Farhan Khaleel (Asian Pacific Journal of Cancer Biology, 2026)
Introduction: The immune system plays an important role in controlling cancer development. Leukemia, a malignant disorder of hematopoietic tissues, is characterized by the abnormal proliferation of white blood cells. Unlike solid tumors, leukemia involves a systemic increase in aberrant blood cells rather than localized masses. This inflammatory condition is driven by immune mechanisms involving pathogenic cytokines, among which Interleukin-33 (IL-33) plays a complex and dual role. IL-33 influences the immune system and the tumor microenvironment (TME), potentially promoting or inhibiting leukemia progression depending on the context. A deeper understanding of its mechanisms could pave the way for innovative treatments targeting the IL-33 axis. Methods: This study aimed to evaluate specific biochemical, hematological, and molecular markers in patients with leukemia. Conducted from June 1, 2024, to September 1, 2024, the study included 60 Iraqi patients with leukemia and 30 healthy controls. Serum levels of interferon regulatory factor 8 (IRF8) and transforming growth factor-beta (TGF-β) were measured using Enzyme-Linked Immunosorbent Assay (ELISA). Single-nucleotide polymorphisms (SNPs) of the IL-33 gene (rs928413) were assessed using Polymerase Chain Reaction (PCR) with a resistance mutation system. Results: Revealed a highly significant increase in IRF8 levels in leukemia patients compared to controls (P < 0.0001), suggesting a strong association with the pathological state. While overall TGF-β levels did not differ significantly between groups, analysis of genetic polymorphisms indicated a potential influence of the IL-33 rs928413 genotype on TGF-β regulation in patients. Specifically, the GG genotype was associated with the highest IRF8 and TGF-β levels in patients. Although allele distribution of IL-33 rs928413 did not show a direct association with increased risk in this sample, the findings suggest a complex interplay between IL-33 gene polymorphisms, IRF8, and TGF-β in leukemia. Conclusion: Leukemia patients exhibit elevated immune markers, particularly IRF8, which may play a significant role in disease onset and progression. Further studies are warranted to elucidate the molecular mechanisms linking IL-33 gene polymorphisms to IRF8 and TGF-β function in leukemia, and to explore their potential as therapeutic targets or prognostic markers.